Clinical Audit to Assess Upper Airway Ultrasound Skills in Anaesthesia Trainees - Ambekar, Atul A (Cureus, 2020)
This audit looks at upper airway ultrasound skills and basic knowledge of anaesthesia trainees. The implementation took place in a District General Hospital in the United Kingdom where upper airway ultrasound is not a part of formal training. Seventeen anaesthetic trainees were given hands-on experience of upper airway ultrasound and were asked to fill in a questionnaire. The result showed a rapid learning curve for assessing cricothyroid membrane localisation, but difficulty in oesophageal identification. A potential plan to improve this skill was proposed and if implemented, will help all trainee anaesthetists in the present and future to develop this skill.